Pemberian Lakuto terhadap Glukosa Darah Penderita Diabetes Melitus Tipe 2 - Eliza Eliza; Darlita Aprilianti; Yunita Nazarena; Terati Terati; Sumarman Sumarman (Jurnal Ilmiah Kesehatan (JIKA), 2022)
Diabetes Mellitus is a chronic disease characterized by hyperglycemia and glucose intolerance in the blood because the pancreas is unable to produce insulin. The risk factors that led to diabetes mellitus are reversible and irreversible. The study was aimed at recognizing the effect that pumpkin and tomato pudding (lakuto) have on decreasing blood glucose levels in type 2 diabetesmellitus in Puskesmas Padang Selasa Palembang. It is a quantitative research using quasi-experiment design with pretest and posttest with two groups design. The subjects were mostly 61-70 years old and female. Average levels of blood glucose before treatment are 329,33 mg/dl in the treatment group and 314,07 mg/dl in the control groups. Whereas the average blood glucose level after treatment was 301,43 mg/dl in the treatment group and 304,00 mg/dl in the control groups. The result showed the effects of pumpkin and tomato pudding (lakuto) on blood glucose levels in diabetes mellitus type 2 in Puskesmas Padang Selasa Palembang (p-value=0,000). This suggests that pumpkin and tomato pudding (lakuto) may lower blood glucose levels in patients with type 2 diabetes mellitus.